Fighting, Alcohol and Offending: Interventions Targeting Aboriginal Girls (YAWG) - Wilson, Mandy; Jones, Jocelyn; Butt, Julia; Morrison, Daniel; Wilkes, Edward (2019)
The YAWG project was conducted by researchers at the National Drug Research Institute, Curtin University, in partnership with Wungening Aboriginal Corporation. It used a participatory action approach to collect in-depth data around the experiences of 38 Aboriginal girls and young women (10-18 years) around drinking (alcohol), fighting and offending and aimed to develop a health promotion resource around these issues. The research and analysis was guided by young women’s input, and identified that some service providers may not understand the lived experiences of young Aboriginal women and their barriers to seeking help around drinking, fighting and offending. To address this, the YAWG website was developed as a resource for service providers who work or come into contact with young Aboriginal women and girls.